Parameters Used for Evaluation of the Response to Treatment with Recombinant Human Growth Hormone in Paediatric and Adult Populations in Poland: Review - Kotkowiak, Agata; Łabuda, Mikołaj; Szema , Agnieszka; Sikora, Jakub; Knychalska, Karolina; Królikowska, Klaudia; Słojewska, Aleksandra; Sowińska, Teresa; Mentel, Oliwia; Bogucka, Adrianna (Journal of Education, Health and Sport, 2025)
Introduction and purpose Recombinant human growth hormone (rhGH) therapy has been the standard treatment for paediatric short stature for many years, and a therapeutic option for the replacement therapy of growth hormone deficiency in the post-growth patient population. Each country providing rhGH treatment has its own programms based on national recommendations and international guidelines. The aim of this review was to discuss selected parameters used for assessment of the response to rhGH treatment in the paediatric and the post-growth adult populations, using the example of Poland. Description of state of knowledge The rhGH therapy requires thorough monitoring to minimize potential adverse effects and to optimize treatment outcomes. Due to the differences in the final therapeutic effects of rhGH between pediatric and adult cohorts, different parameters are used to assess treatment efficacy. In children and adolescents, anthropometric measurements reflecting growth are primarily utilized. Considering the systemic effects of the rhGH, metabolic parameters are evaluated in both populations. In adults, additional assessments include quality of life, measured using standardized questionnaires, and bone mineral density. Computer predictive models can also be used to monitor the treatment. Conclusion Growth hormone therapy has been associated with a range of well-documented benefits both paediatric and adult populations. However, its administration necessitates comprehensive monitoring based on standardized parameters specific to each patient cohort.